1984
DOI: 10.1161/01.str.15.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Flow patterns in the human carotid artery bifurcation.

Abstract: SUMMARY To elucidate the connection between blood flow and the localized genesis and development of atherosclerosis and thrombosis at the human carotid artery bifurcation, detailed studies of the flow patterns and distributions of fluid velocity and wall shear rate in this region were carried out using a transparent segment of the carotid artery, prepared from a human subject postmortem, and cinemicrographic techniques.It

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0
3

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(96 citation statements)
references
References 24 publications
3
90
0
3
Order By: Relevance
“…High axial velocities near the flow divider and areas of flow separation and reversal on the side of the bulb opposite to this divider were also observed under conditions of steady flow in rigid models1 2 and studies on undistensible vessels in vitro. 4 In this situation, however, the region of separation is fixed and a well-defined stable secondary flow structure can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…High axial velocities near the flow divider and areas of flow separation and reversal on the side of the bulb opposite to this divider were also observed under conditions of steady flow in rigid models1 2 and studies on undistensible vessels in vitro. 4 In this situation, however, the region of separation is fixed and a well-defined stable secondary flow structure can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have proposed various geometric risk factors for the incidence of atherosclerotic plaques, e.g., increased bifurcation angle and enhanced differences in area ratios including the flare, proximal curvature, and tortuosity of ICA. Computational fluid dynamics (CFD) simulations have been carried out to calculate various atherogenic hemodynamic parameters, i.e., low wall shear stress (WSS) and high oscillatory shear index (OSI), at carotid artery bifurcation (14,18,19,21,22,29). These morphometric and hemodynamic studies suggested the presence of atherosclerotic plaques near the sinus region of carotid artery bifurcation because of low WSS and high OSI.…”
mentioning
confidence: 99%
“…This results in an increased tendency to thrombosis and increase in leukocyte adhesion, smooth muscle proliferation and endothelial apoptosis. 15,16) Considering the fact that the RCA is also exposed to this type of mechanical affect, especially in its crux, and low shear stress may trigger or accelerate the atherosclerotic involvement here, bifurcation between right posterior descending artery and right posterolateral artery is more likely to be targeted to the atherosclerotic process than proximal segments of the RCA. Therefore, flow runoff of the venous bypass grafts anastomosed proximally to the crux may be at risk for occlusion in long-term.…”
Section: Discussionmentioning
confidence: 99%